062 A novel scoring system for the respiratory health of children with spinal muscular atrophy type 1. (December 2018) - Robinson, V; Edel, L; Grime, C; Chan, E
Abstract : Background: Spinal muscular atrophy type 1 (SMA 1) typically presents before 6 months of age with progressive muscle weakness, bulbar dysfunction and respiratory failure. Nusinersun is the first treatment available for SMA I and it has been shown to improve survival and gross motor function compared to placebo; however, little is known about its effect on respiratory status. While receiving Nusinersun, motor skills are monitored using standardised scoring systems; however, there is no relevant respiratory scoring tool for this patient group. The aims of this study is to develop a composite scoring system to assess the respiratory status of SMA I patients and to describe the baseline status of these children prior to receiving Nusinersun using the scores. Methods: We developed The Great Ormond Street SMA I Respiratory (GSR) score to evaluate the respiratory status of the children with SMA 1 under our care. We generated scores 1–19, with lower values representing better respiratory status (table 1). The key discriminators of respiratory health are the reliance on chest clearance techniques and the need for non-invasive ventilation (NIV). Results: Seventeen SMA I children were under our care and all undergoing treatment with Nusinersun. The median age of diagnosis is 6 months at which point the median GSR score was 2/19. Treatment with Nusinersun was initiated at a median of 90 days following diagnosis at which point the GSR score increased to a median of 10/19. The median age of initiating NIV was 8 months. Discussion: At the initiation of Nusinersun, an increased GSR scores reflected the introduction of airway clearance techniques and in 10 cases, non-invasive ventilation. The next step will be to use this tool to track the respiratory status of children while they are receiving Nusinersun, with these scores as a baseline.